Investigate How KPR BTN Purchase Decisions are Impacted By Price, Brand Awareness, and Trust - Rezky Oktafiandi; Yolanda Yolanda (Return : Study of Management, Economic and Bussines, 2023)
The goal of this study is to examine how pricing, brand recognition, and trustaffect consumers’ decisions to use KPR BTN. The analysis of multiple linearregressions was used in this study. The primary data used in this study camefrom respondents’ answers to questions they were asked. All KPR BTN usersmake up the sample for this study. The findings of this study show that price,brand awareness and buyer trust are all simultaneously significant variablesPurposive sampling was the technique ultilized in this study for sampling.The researcher's consideration that the information required can be collectedfrom one specific target group that is able to supply information for theresearch led to the selection of this technique. By distributing questionnairesto BTN KPR clients, primary data was directly collected for research. Whentwo or more independent variables are employed as predictor factors and theresearcher wants to forecast how the state (ups and downs) of the dependentvariable (criteria), multiple regression analysis is used (in addition tolowering their values). The findings of this study also indicated that variablessuch as price and brand awareness had a major impact on purchasingdecisions, whereas variables such as trust did not.